2004
DOI: 10.1016/s0002-9394(03)01148-6
|View full text |Cite
|
Sign up to set email alerts
|

Ocular screening in severe acute respiratory syndrome

Abstract: PURPOSE: To investigate the ocular manifestations of patients with severe acute respiratory syndrome (SARS) and to monitor the possible ocular complications arising from the treatment regimen with high-dose systemic corticosteroid drugs. DESIGN: Prospective, observational cohort case series. METHODS: Ninety eyes from 45 patients with the diagnosis of SARS during an epidemic outbreak in Hong Kong were analyzed. Relevant medical and ophthalmic histories were taken. Ophthalmic examinations, including best-correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Other outcomes that have been followed-up in SARS patients are reported in Table V. A 2004 study by Yuen et al (35) found no eye pathologies in this cohort. A 2004 case series study by Tsai et al (36) followed up patients who developed limb weakness related to critical illness neuropathy (CIN) and myopathy (CIM) and sensory deficits following infection.…”
Section: Resultsmentioning
confidence: 81%
“…Other outcomes that have been followed-up in SARS patients are reported in Table V. A 2004 study by Yuen et al (35) found no eye pathologies in this cohort. A 2004 case series study by Tsai et al (36) followed up patients who developed limb weakness related to critical illness neuropathy (CIN) and myopathy (CIM) and sensory deficits following infection.…”
Section: Resultsmentioning
confidence: 81%
“…Neither MERS-CoV nor SARS-CoV described eye symptom [3][4][5] , although the presence of the virus was confirmed by polymerase chain reaction in tears of patients with SARS-CoV infection 6 . Recent report showed that conjunctivitis symptoms were found in a small number of adult patients diagnosed with COVID-19, with positive results of viral nucleic acid in conjunctival sac swab samples 7 .…”
Section: Introductionmentioning
confidence: 91%
“…The presence of ocular pathology other than conjunctivitis in patients with SARS-CoV-2 infection has yet to be described. Yuen et al [12] evaluated 45 patients during the epidemic outbreak of SARS in Hong Kong and did not observe any ocular manifestations. However, retinal disorders such as retinal vasculitis, retinal degeneration, and blood-retinal barrier breakdown have all been reported in experimental animal models of coronavirus infection [13,14].…”
Section: Ocular Manifestations In Patients With Covid-19mentioning
confidence: 99%